Effectiveness of GPOvirS30 for the Treatment of Naïve HIV Patients in Pathumthani Hospital: a 5-Year Experience - Sitaposa, Pratya (Journal of Health Science of Thailand, 2017)
The quality of life of HIV–infected patients in Thailand has been improved due to widely use of the antiretroviral drug - GPOvirS30. The incidence of opportunistic infection and mortality rate markedly decreased. However, compliance and adherence of the treatment were limited by adverse drug events. The objective of this study was to assess long term effectiveness, side effects and incidence of immune reconstitution inflammatory syndrome (IRIS) among treatment naïve HIV–infected patients who were treated with GPOvirS30 during 2002 – 2007 at Pathumthani hospital. There were altogether 148 cases. The Mean (IQR) baseline CD4 cell count was 68.4 cells/mm3 (ranging from 1 – 287). Treatment effectiveness was observed in 30 cases (20.3%) who had the mean CD4 cell count increased to 601.8 (243 – 1,402) cells/mm3 after 76.7 months of continuous treatment; and the plasma viral load was undetectable (lower than 50 copies/ml). Adverse events including lipodystrophy, rash, elevated ALT and peripheral neuropathy were detected in 43.2%, 13.5%, 11.5% and 8.8% of patients, respectively. Twenty-six 26 patients (17.5%) receiving GPOvisS30 developed IRIS including tuberculosis IRIS (8.8%), cryptococcosis IRIS (3.4%) and mycobacterium avium complex IRIS (0.6%). In conclusion, GPOvirS30 was quite well effective in increasing CD4 cell counts and suppressing plasma viremia over five years follow–up period. Its important complication, lipodystrophy was an obstacle for long term compliance. To avoid this problem, further studies to determine risk factors and develop appropriate screening test are needed.